Entrepreneurial knowledge and skill exposure in vocational education: development of a new assessment scale - Abede Mack; Katelynn Carter-Rogers; Priscilla Bahaw; Ayanna Stephens (Springer, 2024)
Abstract Appetite for entrepreneurship education (EE) among vocational students has surged dramatically, driven by persistent challenges of unemployment. As a result, vocational institutions are increasingly focused on how much entrepreneurship exposure students receive, particularly how frequently instructors impart core business knowledge and skills to meet growing demand. However, despite this focus, existing measures primarily assess the overall impact of EE by gathering self-reported data on student attitudes with specific metrics for the frequency of exposure to these vital competencies still lacking. To address this gap, the Vocational Education Entrepreneurship Knowledge and Skills (VEEKS) Scale has been developed to assess the extent of exposure that technical and vocational education and training (TVET) institutions provide to students regarding entrepreneurial competencies. This scale focuses specifically on essential business knowledge and soft skills crucial for entrepreneurial success. With a total sample size of 446, an EFA (n = 180) and CFA (n = 266) determined that business knowledge and soft skills exposure was an acceptable model for measuring VEEKS exposure. Contributing to theory, this measure shifts the focus in EE literature from impact to the exposure of key competencies-knowledge and skills. By moving beyond attitude-based assessments, the scale provides valuable practical insights for TVET institutions, supporting curriculum reform, instructor training, and strategic marketing.